Vancomycin Monitoring for Treatment of Acute Pulmonary Exacerbations of Adult Cystic Fibrosis Patients - Darrell Smith; James Sanders; Marguerite Monogue (Pulmonary Medicine)
Conclusion: In adult pwCF, the incidence of AKI was similar between AUC and trough monitoring cohorts; however, AUC monitoring achieved therapeutic targets sooner with fewer regimen modifications without significantly increasing the number of concentrations compared to trough monitoring.